Synthesis, Antidiabetic Evaluation and Bioisosteric Modification of Quinoline Incorporated 2-pyrazoline Derivatives - Kumar, Abhishek; Kumar, Pankaj; Shetty, Chaithra Raju; James, Jainey Puthenveettil; Shetty, Honey Chandrashekhar (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Diabetes mellitus is a pervasive illness worldwide with many progressively increasing complications day by day. The quinoline nucleus is important heterocyclic moiety with different biological activities. Due to their pivotal role in different biological processes they are well explored as therapeutic agents and some of them have exhibited antihyperglycemic activity. Different substituted pyrazoles have been accounted for their in vivo antidiabetic activity, but we concentrated to substituted pyrazoline derivatives in the quest for novel basic classes of medications inhibiting the action of the ATP-K+ beta cell pancreatic membrane channel, prompting the release of insulin. Materials and Methods: In the present study, 1-(4-(7-Chloroquinolin-4-yl oxy) phenyl ethanone and 1-(4-(7-Chloroquinolin-4-yl amino) phenyl ethanone was synthesized by nucleophilic substitution of 4-Chloro of 4,7-dichloroquinoline with substituted 4-hydroxy acetophenone and 4-amino acetophenone in DMF and KOH respectively. The amino linked chalcones and oxo linked chalcones was synthesized by Clasein Schmidt condensation with different substituted aromatic aldehydes. Finally substituted pyrazolines (ACP1-ACP10) was synthesized upon cyclisation of oxo linked and amino linked chalcones with hydrazine hydrate. The structures of the final synthesized compounds were characterized by IR, 1H NMR and mass spectra. Results: The final synthesized compounds were evaluated for their in vitro antidiabetic activity by alpha glucosidase inhibition assay. Most of the compounds showed good antidiabetic activity compared to the standard drug acarbose. Conclusion: In-vitro results revealed that a large number of synthesized compounds having good antidiabetic activity. So these compounds are found to be interesting lead molecules for further synthesis as antidiabetic agents.
Keywords: Quinoline; Oxo linked; Amino linked; Chalcones; Pyrazoline; Antidiabetic; activity